Sorghum-wheat productivity and soil nutrient status under Eucalyptus (Eucalyptus tereticornis) boundary plantation in semi-arid region - SIROHI, CHHAVI (Indian Journal of Agroforestry, 2025)
Fast-growing trees, such as eucalyptus (Eucalyptus tereticornis), can be included into agricultural systems to offer a number of advantages over agriculture without trees. In semi-arid regions, windbreaks are typically utilized as a type of agroforestry (AF) to lower the wind speeds for sustainable agricultural production and other ecosystem services. Selecting appropriate crop to reduce competitive interactions in the tree interaction zone is crucial to the sustainability of windbreak agroforestry systems (AFS). It is recommended that well-modified tree-crop integration be established by reducing resource competition and leveraging coactions in order to increase AFS efficiency. A field experiment was carried out with the objective to assess the green fodder yield of sorghum and grain yield of wheat at varying distances (0-3 m, 3-6 m, 6-9 m, 9-12 m, 12-15 m, and 15-18 m) from tree line as affected by six year old eucalyptus boundary plantation in East-West and North-South directions (E-W tree line divide farmlands into two aspects i.e. Northern and Southern and N-S tree line divide into Eastern and western aspects). The green fodder yield of sorghum and grain yield of wheat declined significantly up to 9 and 3 m distance from eucalyptus tree line, respectively in all the four aspects during the study period. The maximum green fodder yield of sorghum and grain yield of wheat (36.2 and 3.33 t/ha) was recorded in north-south row direction of eucalyptus bund plantation. The variable influence of tree line directions on yield in different aspects might be attributed to micro-site enrichment caused by favourable environment due to shade and leaf litter addition. We also quantified the soil  pH, EC, available nitrogen (N), phosphorus (P) and potassium (K) under six year old eucalyptus boundary plantation at varying distances (0-3 m, 3-6 m, 6-9 m, 9-12 m, 12-15 m, and 15-18 m) in East-West and North-South directions. The organic carbon showed a decreasing trend for SOC from 0-3m to 15-18m and higher organic carbon was recorded in western aspect followed by southern aspect. The available N, P and K also showed decreasing trends for N, P and K from tree line to 15-18m of eucalyptus windbreaks AFS.